Hamburger Hill - Nasatir, Marcia; Carabatsos, Jim; Irvin, John ([Hollywood, CA : Paramount Pictures, 2008)
The men of Bravo Company are facing a battle that's all up hillup Hamburger Hill. Fourteen war-weary soldiers are battling for a mud-covered mound of earth so named because it chews up soldiers like chopped meat. They are fighting for their country, their fellow soldiers and for their lives. War is hell, but this is worse. It's a raw gritty and totally unrelenting dramatic depiction of one of the fiercest battles of the Vietnam War
Title from title screen
Features:'Hamburger Hill : the appearance of reality' featurette,'Medics in Vietnam' featurette, interactive Vietnam War timeline, audio commentary
Director of photography, Peter MacDonald ; editor, Peter Tanner ; music, Philip Glass
Cast: Anthony Barrile, Michael Patrick Boatman, Don Cheadle, Michael Dolan, Don James, Dylan McDermott, M.A. Nickles, Harry O'Reilly, Daniel O'Shea, Tim Quill, Tommy Swerdlow, Courtney B. Vance, Steven Weber, Tegan West
DVD format
With optional English, Chinese or Malay subtitles
Keywords: United States. -- Army. -- Airborne Division, 101st -- Drama; Hamburger Hill, Battle of, Vietnam, 1969 -- Drama; Vietnam War, 1961-1975 -- Drama; Vietnam War, 1961-1975 -- Drama